Pengaruh variasi pemberian Snack bar ubi jalar kedelai hitam terhadap Kadar Superoksida Dismutase (SOD) darah - Ayustaningwarno, Fitriyono; Sabuluntika, Novita (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2014)
Background: Snack bar from sweet potatoes and black soybeans is low GI, fat and calorie snack which haveantioxidant content, such as β-carotene, anthocyanin, isoflavone, and antioxidant activity, so can be an alternativesnack for patients with DM type 2. Antioxidants intake can prevent the oxidative stress that lead micro- and macrovascularcomplications in DM type 2. Antioxidant intake may preserve endogen antioxidant capacity, which is can bedetermined by analyzing SOD concentration.Objective: analyze effect variety of Snack bar from sweet potatoes and black soybeans consume to SOD concentration.Methods: experimental post-pretest research used 3 varieties of sweet potato’s color (red, yellow, and purple)interventions. SOD concentration was analyzed by colorimetric. Statistic data was analyzed by dependent t-test andOne Way Anova.Results: No different between groups interventions Snack bar from purple, yellow or red sweet potatoes (p=0,122).Group with snack bar from purple sweet potatoes intervention has lowest SOD decreasing percentage among otherintervention groups.Conclusion: Consume snack bar form purple sweet potatoes and black soybeans can preserve SOD concentrationbetter than consume snack bar form yellow or red sweet potatoes and black soybeans